2020
DOI: 10.1111/rda.13621
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in microorganisms isolated in a bull semen stud

Abstract: Many microorganisms from various sources may be present in ejaculates of bulls. This study identified and isolated bacteria from bull sperm samples in a commercial stud and evaluated their resistance to antibiotics. The number of colony‐forming units was determined in semen samples collected at distinct steps during freezing and thawing. The minimum inhibitory concentration and the minimum bactericidal concentration were determined for four antibiotics commonly used in commercial studs. A total of 135 microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Although such high concentrations are commonly not present in the insemination straws, we suggest to target the antibacterial supplementation of insemination doses against the selected species. Especially, bacterial species resistant to frequently used antibiotics may represent a high risk [ 33 ]. For the future, it would be interesting to monitor intracellular Mg and Ca concentration in order to investigate if the environment with a reduced Mg and Ca concentration would be directly reflected in reduced Mg and Ca amounts inside the cell, and thus a lower availability of these cations for the metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although such high concentrations are commonly not present in the insemination straws, we suggest to target the antibacterial supplementation of insemination doses against the selected species. Especially, bacterial species resistant to frequently used antibiotics may represent a high risk [ 33 ]. For the future, it would be interesting to monitor intracellular Mg and Ca concentration in order to investigate if the environment with a reduced Mg and Ca concentration would be directly reflected in reduced Mg and Ca amounts inside the cell, and thus a lower availability of these cations for the metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors found 103-106 CFU/mL in five bulls analysed after collection at an insemination centre [59] and 50.38 ± 16.29 CFU/mL in thawed cryopreserved bull semen collected under field conditions [60]. A recent study [61] isolated 135 microorganisms from 25 genera from 174 frozen-thawed semen collected from artificial vaginas and analysed at different periods of the conservation process. However, there is scarce information about the microbiological quality of semen collected in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In one study [61], all 55 microorganisms evaluated were resistant to penicillin, contained in INRA96 ® , and all but one microorganism were resistant to tylosin and lincomycin, both present in BIOXcell ® and AndroMed ® . In a study of bull semen, resistance to all tested antibiotics was observed in 22% of all isolates from 135 different microorganisms, whereas only 3.9% of the isolates were inhibited by the antibiotics stipulated in EC Directive 88/407 [61]. A study on the bacterial load in frozen bull semen found that Gram-negative and -positive bacteria behaved differently in response to different antibiotics [62].…”
Section: Discussionmentioning
confidence: 99%
“…and Pseudomonas spp. [ 82 ]. Similar resistance patterns were also observed in semen samples collected from boars [ 83 ] and rams [ 13 ].…”
Section: Discussionmentioning
confidence: 99%